Dr. V. Raghavan shashtyabdapurti felicitation volume; a souvenir of the 61st birthday celebrations and a collection of essays contributed in his honour by his friends, colleagues, and students on that occasion - Raghavan, V. (Dr. V. Raghavan Shashtyabdapurti Felicitation Committee, Kuppuswami Sastri Research Institute, 1971)
Festschrift honoring the Indian scholar Venkataram Raghavan, 1908-; comprises articles chiefly on indology.